Characteristic Analysis of the Gravity Unloading Device for the Satellite Simulation Experiment - Liu, Mingtao; Bai, Jiaxuan; Chen, Gang; Zhang, Qi (Journal of Research in Science and Engineering, 2026)
With the growing complexity of space station missions, space manipulators play an increasingly important role in extravehicular operations. However, the microgravity environment imposes stringent requirements on ground verification tests, making accurate gravity unloading simulation a critical challenge. This paper proposes a theoretical design method for a gravity unloading system based on an equivalent end-stiffness mechanism for space manipulator ground testing. The manipulator topology is analyzed, and force and stiffness models including end air buoyancy are established. The effects of end air buoyancy, air-bearing spring stiffness, and unloading-position scale parameters on the unloading rate are investigated. In addition, the design principles of the ground test system are discussed, with emphasis on the consistency criterion between ground tests and space missions. The test process is optimized using an orthogonal test method to obtain comprehensive performance parameters through limited experiments while ensuring verification reliability and protecting key components. The results determine the feasible range of unloading positions and provide theoretical and engineering guidance for the structural design of manipulator unloading devices and the preliminary selection of test parameters. Future work should further improve gravity unloading efficiency and real-time monitoring accuracy over the manipulator’s full workspace.